Randomised controlled trial with parallel process evaluation and health economic analysis to evaluate a nutritional management intervention, OptiCALS, for patients with amyotrophic lateral sclerosis: study protocol - Simon Waterhouse; Chin Maguire; Vanessa Halliday; Cindy Cooper; Elizabeth Coates; Mike Bradburn; Pamela J Shaw; Ammar Al-Chalabi; Tracey Anne Young; Christopher J McDermott; Wendy Baird; Paul Norman; et al. (BMJ Open)
Introduction Amyotrophic lateral sclerosis (ALS) is a devastating illness that leads to muscle weakness and death usually within around 3 years of diagnosis. People with ALS (pwALS) often lose weight due to raised energy requirements and symptoms of the disease presenting significant challenges to taking adequate oral diet, with those who lose more weight being at a greater chance of earlier death. There is also some evidence to suggest that a higher calorie diet may benefit the disease course in pwALS, but further research is needed.Methods and analysis Two armed, parallel group, superiority, open labelled, randomised controlled trial, with internal pilot, to assess the effectiveness of an early high calorie diet on functional outcomes in ALS, comprising two treatment arms: (1) standard care, (2) standard care with additional active management using the OptiCALS complex intervention to achieve a high calorie diet (initially randomised 1:1, then 1:2 following a protocol amendment). Using a food first approach, pwALS will be encouraged and supported to follow a diet that meets an individualised calorie target from food before prescribing oral nutritional supplements. 259 pwALS will be recruited from up to 20 ALS centres across the United Kingdom and Ireland and followed up for a period of 12 months. Primary outcome is functional change measured over 12 months, using the Revised Amyotrophic Lateral Sclerosis Functional Rating Scale. Secondary end points include measures of functional health, quality of life, calorie intake and weight, as well as time to gastrostomy and survival. A health economic analysis and process evaluation will also be undertaken. Participant recruitment is expected to complete in September 2025, and participant follow-up is expected to complete in September 2026. The results of this study are expected in March 2027.Ethics and dissemination The trial was approved by Greater Manchester—North West Research Ethics Committee, reference 20/NW/0334 on 8 September 2020. We will publish the study findings in peer-reviewed academic journals and present at local, national and international conferences where possible.Trial registration number ISRCTN30588041.